Inhibition of the renin angiotensin system decreases fibrogenic cytokine expression in tacrolimus nephrotoxicity in rats - TUĞLULAR, ZÜBEYDE SERHAN (ELSEVIER SCIENCE INC, 2006)
The aim of our study was to investigate the influence of angiotensin-converting enzyme (ACE) inhibition and angiotensin II receptor blockage on the renal function by light microscopic and immunohistochemical findings in a rat model of tacrolimus nephrotoxicity. thirty-two male Wistar rats were divided into four groups of eight: G1 = control group; G2-G3, G4 = Tacrolimus (Tac) 1 mg/kg/d intraperitoneally (ip); G3 (Tac + Q) = ip Tac and peroral quinapril 10 mg/kg; and G4 (Tac + V) = Tac and valsartan 40 mg/d. Serum blood urea nitrogen (BUN), creatinine, and creatinine clearance were measured before and at the end of the study period. Renal tissues were assessed for light microscopic findings of tacrolimus toxicity. Transforming growth factor-beta, VEGF, PDGF, BMP-7, and interleukin-6 (IL-6) expression were semiquantitatively scored after immunohistochemical staining. At the end of the study period serum BUN and creatinine levels were increased in all groups, but creatinine clearance was not significantly changed between the groups. Afferent arteriolopathy was significantly less pronounced in G3 versus G2 and G4. Interstial fibrosis was significantly less pronounced in G3 and G4 versus G2. TGF-beta, PDGF, and IL-6 expression were significantly increased in G2, G3, and G4 compared to G1, and in G2 compared to G3 and G4. BMP-7 expression was significantly decreased in G2, G3, and G4 compared to G1, whereas the differences between G2, G3, and G4 failed to reach statistical significance. In conclusion, the results of our study suggested that renin angiotensin inhibition down-regulates fibrogenic cytokine expression in rats displaying tacrolimus nephrotoxicity.
Keywords: ENDOTHELIAL GROWTH-FACTOR; TGF-BETA; MESANGIAL CELLS; CYCLOSPORINE NEPHROTOXICITY; RENAL-TRANSPLANTATION; FIBROSIS; IMMUNOSUPPRESSION; RECEPTORS